2014
DOI: 10.1111/ggi.12378
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life of older adults with cancer in Korea

Abstract: The findings suggest that efforts to assess physical functioning with more attention and enhance optimism should be emphasized in interventions for older adults with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
(52 reference statements)
1
22
2
Order By: Relevance
“…The occurrence of gastrointestinal symptoms and the side-effects associated with cancer treatment reduce food intake and induce weight loss, impacting mobility and the capacity to perform daily-life activities. It is also known that reduced performance and mobility have a negative impact on social interactions and emotional health of the sufferers [27]. Therefore, even though social and emotional QoL and nutritional status were found to be correlated with each other in our study, we suggest that one effect may not necessarily be a direct consequence of the other, but possibly an indirect relationship, in which one exacerbates the other via the consequences of impacted social and emotional life.…”
Section: Discussioncontrasting
confidence: 69%
“…The occurrence of gastrointestinal symptoms and the side-effects associated with cancer treatment reduce food intake and induce weight loss, impacting mobility and the capacity to perform daily-life activities. It is also known that reduced performance and mobility have a negative impact on social interactions and emotional health of the sufferers [27]. Therefore, even though social and emotional QoL and nutritional status were found to be correlated with each other in our study, we suggest that one effect may not necessarily be a direct consequence of the other, but possibly an indirect relationship, in which one exacerbates the other via the consequences of impacted social and emotional life.…”
Section: Discussioncontrasting
confidence: 69%
“…Compromised QoL among older adults has been associated with various factors including social factors. 29 In the present study, sociodemographic characteristics were associated with compromised QoL, indicating that better life conditions might lead to a better QoL for older adults. Older adults have shown that the accumulation of material wealth, satisfaction with work and family ties are factors that lead to an enhanced QoL later in life.…”
Section: Discussionmentioning
confidence: 49%
“…Compromised QoL among older adults has been associated with various factors including social factors . In the present study, sociodemographic characteristics were associated with compromised QoL, indicating that better life conditions might lead to a better QoL for older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Most 1 , Seong-Hyung Choi 1 studies about activity limitations or functioning of cancer survivors are limited to specific cancer diagnoses (Kim et al, 2012;Sim et al, 2014), or conducted without comparison groups (Yoon et al, 2014). Additionally, the data about activity limitations disparities among sex and age subgroups is limited.…”
Section: Introductionmentioning
confidence: 99%